PERANAN LEMBAGA PENDIDIKAN TENAGA KEPENDIDIKAN DALAM PENGEMBANGAN KUALITAS PENDIDIK DAN TENAGA KEPENDIDIKAN PENDIDIKAN NON FORMAL - D. Sudjana (JIV-Jurnal Ilmiah Visi, 2006)
To provide access to education for all Indonesians, the government develops both formal and nonformal education both of which are to produce qualified man power as stated in the Acts of No. 20, 2003. However, to do this non-formal education should have teachers and education personnel fulfilling the requirements of quality and quantity. This article discusses a number of problems in providing teachers and education personnel for non formal education. It invites the universities organizing teachers training to develop programs for the teachers of nonformal education. Due to the big number of the teachers with the variety of specialties needed at present and in the future, this article suggests developing and strengthening the existing teacher training program at the university to become a Faculty of Non Formal Teachers.